STRATEGI PRODUK, PENETAPAN HARGA, PROMOSI, DAN LOKASI DALAM MENINGKATKAN PENJUALAN PRODUK ARRUM (Studi : PT.Pegadaian Syariah Cabang Simpang Sekip Kota Bengkulu) - Elvira, Rini (Institut Agama Islam Bengkulu, 2017)
Within the last five years PT. Pegadaian Syariah Cabang Simpang Sekip Kota Bengkulu have difficulty in increasing the number of the customerÂ product ARRUM. Thus causing often do not achieve the sales target. This research attempt formulated product strategy, pricing, promotions, and location can be used as an attempt to increase the number of customer product ARRUM by using SWOT analysis. The results of research to formulate 6 (six) product strategy, namely, (1) maintaning corporate identity,(2) maintaining consistent product services, (3) consistenly maintaining value estimates are a product, (4) pay more attention to the comfort of the customer, (5) using a service-based information tecnology for ease of transactions, and (6) maintainingÂ the quality of product. The Four (4) pricing strategies, namely, (1) maintaining consistent estimates of the financing, (2) administration costs of maintaining a consistenly competitive, (3) extend the term of payment, (4) set the ujrah competitively. Three (3) promotional strategy, (1) expanding media promotion, (2) promotion with a fixed frequency which pay attention to cost efficiency, (3) optimize the capabilities of your existing salespeople. Two (2) distribution strategy (location, consisting of, (1) expand the areas of marketing, and (2) more focus on the market potential of the environment siteÂ PT. Pegadaian Syariah Cabang Simpang Sekip Kota Bengkulu.Keywords : strategy, product, price, promotion, location, sales